The Mediating Effects of Organizational Commitment and Job Satisfaction on Perceived Organizational Support Effects Toward Employee Performance of Account Officer in Indonesia - Hidayat, Deva; Ardiyanti, Niken (Jurnal Manajemen (Edisi Elektronik), 2025)
Employee performance is one of the factors that has attracted at-tention in the banking industry. The finance-to-deposit ratio of the banking industry in Indonesia has been growing since 2023. How-ever, along with that growth, the number of nonperforming loans also keeps rising. Moreover, the MSME credit portion hasn’t reached the targeted point of 30%. Account Officers play a vital role in the micro and MSME segment distribution. Data is collect-ed from 381 bank account officers. This study aims to examine the effects of perceived organizational support on job satisfaction, organizational commitment, and employee performance. A partial mediating effect of organizational commitment and job satisfaction was also found in the relationship between perceived organiza-tional commitment and employee performance. The result of this research is that it gives insight into how banking companies are able to improve employee performance.